Congruence between the self-reported empathy of nurses in primary health care and the user’s perception of the empathic relationship - Dullius, Luana (2022)
Objective: To investigate the congruence between nurses’ self-reported empathy (IRI) and the professional’s perceived empathy by the user (CARE).Material and Methods: The study included 36 nurses working in Primary Health Care (PHC) in the city of Porto Alegre (Rio Grande do Sul) and 166 users attended by these professionals. Spearman’s correlation tests were used to check the congruence between IRI (Interpersonal Reactivity Index) e a CARE (Consultation and Relational Empathy), as well as Mann-Whitney and Kruskal-Wallis tests to analyze the association between IRI and CARE with variables such as occupational stress and performance characteristics of women. professionals.Results: No associations were found between IRI and CARE (rho = 0.41, p = 0.596). However, it was found that the user’s perception of the professional’s empathy varied according to stress levels (H (3) = 9.149, p = 0.027).Discussion: Recognizing the impact of stress in the way the professional expresses empathy allows actions to promote and prevent health to be developed in the workplace and impact not only the health of the worker but also the health of the user served.